Symmetrical peripheral gangrene complicating recurrent cholangiocarcinoma: a case report - Yang, Chao; Hu, Jing; He, Xiaoping; Fan, Xianming (Journal of the Pakistan Medical Association, 2025)
Symmetrical peripheral gangrene (SPG) is a rare, life-threatening complication often linked to severe illnesses. This case report describes the case of a 28-year-old male with recurrent cholangiocarcinoma who developed SPG after being admitted to the intensive care unit (ICU) for septic shock. Despite initial survival with antibiotics, vasopressors, and supportive care, he refused amputation, leading to secondary infection and death. Early management of septic shock and disseminated intravascular coagulation (DIC), with cautious vasopressor use, is crucial to prevent SPG. Keywords: Cholangiocarcinoma, Symmetrical peripheral gangrene, Sepsis, Diffuse intravascular coagulation.